Upregulation of Anti-Angiogenic miR-106b-3p Correlates Negatively with IGF-1 and Vascular Health Parameters in a Model of Subclinical Cardiovascular Disease: Study with Metformin Therapy - Sherin Bakhashab; Josie O’Neill; Rosie Barber; Catherine Arden; Jolanta U. Weaver (Biomedicines, 2024)
Well-controlled type 1 diabetes mellitus (T1DM) is regarded as a model of subclinical cardiovascular disease (CVD), characterized by inflammation and adverse vascular health. However, the underlying mechanisms are not fully understood. We investigated insulin-like growth factor-1 (IGF-1) and IGF-binding protein-3 (IGFBP-3) levels, their correlation to miR-106b-3p expression in a subclinical CVD model, and the cardioprotective effect of metformin. A total of 20 controls and 29 well-controlled T1DM subjects were studied. Plasma IGF-1, IGFBP-3 levels, and miR-106b-3p expression in colony-forming unit-Hills were analyzed and compared with vascular markers. miR-106b-3p was upregulated in T1DM (p < 0.05) and negatively correlated with pro-angiogenic markers CD34+/100-lymphocytes (p < 0.05) and IGF-1 (p < 0.05). IGF-1 was downregulated in T1DM (p < 0.01), which was associated with increased inflammatory markers TNF-α, CRP, and IL-10 and reduced CD34+/100-lymphocytes. IGFBP-3 had no significant results. Metformin had no effect on IGF-1 but significantly reduced miR-106b-3p (p < 0.0001). An Ingenuity Pathway analysis predicted miR-106b-3p to inhibit PDGFA, PIK3CG, GDNF, and ADAMTS13, which activated CVD. Metformin was predicted to be cardioprotective by inhibiting miR-106b-3p. In conclusion: Subclinical CVD is characterized by a cardio-adverse profile of low IGF-1 and upregulated miR-106b-3p. We demonstrated that the cardioprotective effect of metformin may be via downregulation of upregulated miR-106b-3p and its effect on downstream targets.